Preparation of PVP-BiOBr Adsorbent for Efficient Indigo Carmine Dye Removal Using Flow-Circulation Systems - Saowapak Teerasong; Thanakrit Saenghirun; Thanawat Sunthornchainukul; Supinya Thammaso; Apiwat Chompoosor; Suwat Nanan (My University, 2024)
This work presents an adsorptive removal of indigo carmine (IC) dye using a polyvinylpyrrolidone capped bismuth oxybromide (PVP-BiOBr) adsorbent. PVP-BiOBr was synthesized via a simple precipitation method. The morphology and surface chemical structure of the adsorbent were characterized using XRD, SEM, FTIR, and BET analyses. The adsorption isotherm and kinetics were investigated to reveal the mechanism of dye removal. Prepared PVP-BiOBr has a crystallite size of 19.7 nm, with a mean particle size of ∼2 μm and a surface area of 5.14 m2 g–1. The optimum pH for this adsorptive process spanned the range of 4 to 9. Experimental data indicated applicability of the Langmuir isotherm model, and the study confirms a pseudo-second-order kinetics model. The maximum adsorption capacity for IC dye was 208.3 mg g–1. A flow-circulation system was developed for the treatment of IC dye contaminated water samples. PVP-BiOBr was packed inside a column and did not spill into the water sample after treatment. The removal efficiency was ≥90% after 25 min. The PVP-BiOBr adsorbent could be reused for three cycles. This work demonstrates that PVP-BiOBr is a promising candidate as an adsorbent for IC dye removal. Additionally, the flow-based system establishes an automated operation in continuous mode, which is viable for large scale applications.
Keywords: Indigo carmine; Langmuir adsorption model; Polyvinylpyrrolidone; BET theory; Adsorption and biosorption for pollutant removal